Aggregate Consumption and Wealth in the Long Run: The Impact of Financial Liberalization - Malin Gardberg; Lorenzo Pozzi (Research Institute of Industrial Economics (IFN), 2020)
This paper investigates the impact of financial liberalization on the relationship between consumption and total wealth (i.e., the sum of asset wealth and human wealth). We propose a heterogeneous agent framework with incomplete markets where financial liberalization, by signalling a future reduction in the incomplete markets component of consumption growth, increases the current consumption-wealth ratio. From the model, an aggregate long-run relationship is derived between consumption, total wealth and financial liberalization which is estimated by state space methods using quarterly US data. The results show that the trend in the consumption-wealth ratio is well-captured by our baseline liberalization indicator. We find that the increase in this indicator over the sample period has increased the consumption-wealth ratio with about ten to sixteen percent. Additional estimations suggest that financial liberalization has predictive power for aggregate consumption growth, a result that provides support for the incomplete markets channel put forward in the paper.
Keywords: E21; C32; C11; 330; Consumption; Wealth; Financial liberalization; Incomplete markets; State space model